Importance of Sovereign Retail Sukuk for Energy Infrastructure, in View of Increased Shariah Awareness in Uzbekistan - Holboboyev, Olmos; El Amri, Mohamed Cherif; Elamrı, Mohamed Cherıf (İstanbul Sabahattin Zaim Üniversitesi Yayınları, 2023)
The Objective of this paper is to review such complex issues in Uzbekistan as Infrastructure Financing of the Energy sector projects on one hand, and the recent escalating foreign debt on the other hand and propose the applicable and beneficial financing solution. The implementation of the sovereign domestic retail Sukuk in the country is assumed to benefit in facilitating the complex problems under the environment of the increased Shariah awareness of people of Uzbekistan. The paper adopts qualitative approach by conducting the survey, analysis of the literature review, case studies, gathering valid data and documents from official websites. As households and individuals buy Sukuk it will bring to better wealth distribution and increase their stable income. The Government of Uzbekistan may find this research useful for funding its infrastructure projects in energy sector as well as controlling its increasing foreign debt. To the best of the author’s knowledge, this paper is the first for Uzbekistan with thorough review of the situation based on the valuable primary data. In addition, the research confirms the fact of the increased Shariah awareness of the people of Uzbekistan, which started impacting on their financial preferences to avoid dealings with conventional financing and expedite the implementation of Islamic Finance in the country.
Kitap adı: Bilgi Ekonomisi ve Yönetimi Perspektifiyle Dijitalleşme, Finans ve Teknoloji / Editör: İbrahim Güran Yumuşak -- Bölüm adı: Importance of Sovereign Retail Sukuk for Energy Infrastructure, in View of Increased Shariah Awareness in Uzbekistan / Olmos HOLBOBOYEV, Mohamed Cherif EL AMR -- Sayfa aralığı: 317-330 -- Yayıncı: Sabahattin Zaim Üniversitesi Yayınları -- ISBN: 978-625-7558-31-0. -- Tarih: 2023
Keywords: Sovereign Retail Sukuk; Energy infrastructure; Shariah awareness; Uzbekistan